Վճարահաշվարկային համակարգի զարգացման ներկա միտումները - Թամարա Սիրականի Հովակիմյան (ՀՀ ԳԱԱ հրատ.)
В последние годы дискреционные регуляторные подходы, применяемы центральными банками стран (замораживание банковских счетов, запреты на счета), углубляют недоверие к обратимым в стране платежным инструментам, создавая прочную основу для внедрения альтернативных платежных инструментов. In recent years, discretionary regulatory approaches applied by central banks in countries (freezing of the bank accounts,bans on accounts), deepen distrust with respect to the reversible payment instruments of the country, creating a solid basis for the introduction of alternative payment instruments.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ